Partnership for eXtreme Xtallography (PX2)—A state-of-the-art experimental facility for extreme-conditions crystallography: A case study of pressure-induced phase transition in natural ilvaite - Jingui Xu; Dongzhou Zhang; Sergey N. Tkachev; Przemyslaw K. Dera (Matter and Radiation at Extremes, 2022)
Single-crystal x-ray diffraction (SCXRD) is an important tool to study the crystal structure and phase transitions of crystalline materials at elevated pressures. The Partnership for eXtreme Xtallography (PX2) program at the GSECARS 13-BM-C beamline of the Advanced Photon Source aims to provide state-of-the-art experimental capabilities to determine the crystal structures of materials under extreme conditions using SCXRD. PX2 provides a focused x-ray beam (12 × 18 µm2) at a monochromatic energy of 28.6 keV. High-pressure SCXRD experiments are performed with a six-circle diffractometer and a Pilatus3 photon-counting detector, facilitated by a membrane system for remote pressure control and an online ruby fluorescence system for pressure determination. The efficient, high-quality crystal structure determination at PX2 is exemplified by a study of pressure-induced phase transitions in natural ilvaite [CaFe2+2Fe3+Si2O7O(OH), P21/a space group]. Two phase transitions are observed at high pressure. The SCXRD data confirm the already-known ilvaite-I (P21/a) → ilvaite-II (Pnam) transformation at 0.4(1) GPa, and, a further phase transition is found to occur at 22.8(2) GPa where ilvaite-II transforms into ilvaite-III (P21/a). The crystal structure of the ilvaite-III is solved and refined in the P21/a space group. In addition to the ilvaite-I → ilvaite-II → ilvaite-III phase transitions, two minor structural modifications are observed as discontinuities in the evolution of the FeO6 polyhedral geometries with pressure, which are likely associated with magnetic transitions.